Pengaruh Proses Pengolahan Terhadap Sifat Fisika dan Kimia Bubuk Kedelai - Failisnur Failisnur; Firdausni Firdausni; Silfia Silfia (Institution for Industrial Research and Standardization of Industry - Padang, 2015)
Soybean powder is a functional product which contains high protein and isoflavones. Protein and isoflavones can prevent chronic and degenerative diseases. The processing can affect the composition especially protein and isoflavones mainly the physical properties of soybean powder. The purpose of the research was to evaluate the effect of processing on the physical and chemical properties in order to produce soybean powder to develop the applications in food and pharmaceutical industries. The soybean was processed through a few treatments, roasting, soaking, steaming, boiling, and without treatments as a comparator. The results showed that the processing of immersion, roasting, steaming, and boiling decreased bulk density until 0.06, wettability 8 seconds, protein content 10.87%, and crude fiber 4.85%. However, the isoflavone content of soybean powder increased to 0.077% and water content 2.18% compared to soybean powder without processing.ABSTRAKBubuk kedelai merupakan produk fungsional mengandung protein yang tinggi dan isoflavon. Protein dan isoflavon dapat mencegah penyakit kronis dan degeneratif. Proses pengolahan dapat mempengaruhi komposisi terutama protein dan isoflavon serta sifat fisika dari bubuk kedelai. Tujuan penelitian ini adalah untuk mengevaluasi pengaruh proses pengolahan terhadap sifat fisika dan kimia kedelai bubuk guna mengembangkan aplikasi dalam industri makanan dan farmasi. Kedelai diolah dengan beberapa proses, yaitu: penyangraian, perendaman, pengukusan dan perebusan, serta tanpa pengolahan sebagai pembanding. Hasil penelitian menunjukkan bahwa proses perendaman, penyangraian, pengukusan dan perebusan menurunkan densitas kamba hingga 0,06, wettability 8 detik, kadar protein 10,87% dan serat kasar 4,85%. Akan tetapi, kandungan isoflavon bubuk kedelai naik hingga 0,077% dan kadar air 2,18% dibandingkan dengan bubuk tanpa pengolahan.